Epigraphia zeylanica [electronic resource] - Codrington, H. W. (Humphrey William), 1879-1942. http://id.loc.gov/authorities/names/n97876693; Karuṇāratna, Ḍabliv. Saddhāmaṅgala. http://id.loc.gov/authorities/names/n85104202; Paranavitana, Senarat, 1896-1972. http://id.loc.gov/authorities/names/n50051639; Wickremasinghe, Don M. de Z., 1865-1937. http://id.loc.gov/authorities/names/no99036131; Sri Lanka. Purāvidyā Depārtamēntuva. http://id.loc.gov/authorities/names/n80024094; Ceylon. Archaeological Department. http://id.loc.gov/authorities/names/n80024091 ([Colombo] : Printed at the Dept. of Govt. Printing, Sri Lanka (Ceylon) for the Archeological Dept. [etc.], 1904)
Includes transliterated text of the inscriptions. At head of title: Archeological Survey of Ceylon. Digital reproduction. Mode of access: Internet. Description based on print version record.